Primary umbilical endometriosis. (November 2015) - Claas-Quax, M.J.; Ooft, M.L.; Hoogwater, F.J.H.; Veersema, S.
Abstract: Cutaneous endometriosis is a rare condition, especially when it occurs without previous surgery. We report a case of a 27-year old woman with catamenial bleeding from her umbilicus. A MRI, cytological and pathological examination confirmed the diagnosis of endometriosis. We also present a brief review of the literature.